Village Branding: Instruments of Place Brand Identity for Destinations and MSMes in the Tourism Villages - Desideria Murti; Victoria Sundari; Antonius Bima; Gabriel Emerald (LPPM Stikosa - AWS, 2023)
This research aims to discuss the instruments in place of brand identity for destination development and MSMEs in a tourism village. The participatory approach was carried out by conducting the FGDs (Focus Group Discussions) sequence to involve citizens in formulating place branding. The citizens made and identified designs and icons, provided design directions, and gave the feel of a story to the resulting design. In previous research, place branding mainly was carried out in cities or places with dominant government hierarchies. In contrast, this research was conducted in villages and areas with a solid community base because the selected tourism villages were community-based tourism (CBT) villages. In addition, this research also observes how place branding can be done by trying to understand personality association through a participatory process and came from the citizens themselves. This research will contribute to the necessary instrument schemes for forming place branding in the village and community-based contexts. Several findings were noted in this research related to the challenges of MSMEs and destinations in carrying out branding, profit allocation issues, the difference of value or selling unique in formulating branding, the benefits of branding and technology, and challenges in supporting technology application. Based on the findings, this research showed several instrument applications in place branding, including three pillars, i.e., place physics, place practice, and place personality.